(3fhGRd GdhRGfjs - (3YHO Gddg SjO eMeO Hf eMeO Hf YHO Gddg GdhQRGRjs ((3ehQjJGfjG s)
(3ChdgG (B:s
(3GdMeO ddg CeG HYO aNjQ GdYdhe hCaVdgG Yde Gdabg EP jMJGL Edjg LejY GdCfGe hjSJhi ai GdWdH Hg GdNGU hGdYGde hHg jYde Mdjg GdCTjGA hMQeJgG hUMI GdYHGOGJ haSGOgG fhGRd GdYHGOGJ s
(3BNQgG (B:s
(3hSFd Yf ef bGd MSHJ Ydi ChdGOi gd jONd ajg GdCHfGA eY GdBHGA Ce dG s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3fSNI eYfhfI HGdMHQ GdCMeQ s
(3YdjgG eWGdYI hJUMjMGJ s
(3hYdi GdhQbI GdChdi HYV GdJedcGJ s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs